Comparative analysis of endurance, strength and body composition indicators in professional, under-23 and junior cyclists - Alejo, Lidia B.; Montalvo-Pérez, Almudena; Valenzuela, Pedro L.; Revuelta, Carlos; Ozcoidi, Laureano M.; de la Calle, Víctor; Mateo-March, Manuel; Lucia, Alejandro; Santalla, Alfredo; Barranco-Gil, David (Frontiers in Physiology, 2022)
Purpose: To compare endurance, strength and body composition indicators between cyclists of three different competition age categories. Methods: Fifty-one male road cyclists classified as either junior (n=13, age 16.4±0.5 years), under-23 ([U23], n=24, 19.2±1.3 years) or professional (n=14, 26.1±4.8 years) were studied. Endurance (assessed through a maximal incremental test and an 8-minute time-trial), strength/power (assessed through incremental loading tests for the squat, lunge and hip thrust exercises) and body composition (assessed through dual energy X-ray absorptiometry) were determined on three different testing sessions. Results: U23 and, particularly professional, cyclists attained significantly (p<0.05) higher values than juniors for most of the analyzed endurance indicators (time-trial performance, maximum oxygen uptake [VO2max], peak power output [PPO], respiratory compensation point [RCP], and ventilatory threshold [VT]). Significant differences (p<0.05) between U23 and professionals were also found for time-trial performance, PPO and VT, but not for other markers such as VO2max or RCP. Professional cyclists also showed significantly (p<0.05) lower relative fat mass and higher muscle mass levels than U23 and, particularly, juniors. No consistent differences between age categories were found for muscle strength/power indicators. Conclusions: Endurance (particularly time-trial performance, PPO and VT) and body composition (fat and muscle mass) appear as factors that best differentiate between cyclists of different age categories, whereas no consistent differences are found for muscle strength/power. These findings might help in performance prediction and/or talent identification and may aid in guiding coaches in the design of training programs focused on improving those variables that appear more determinant.